Pengaruh Suplementasi Saccharomyces boulardii terhadap Kejadian Diare pada Balita - Pratiwi, Winda Wahyu; Sarbini, Dwi (Jurnal Kesehatan Andalas, 2022)
Diarrhea is a disease that occurs due to viral or bacterial infection in the digestive tract system. Signs of diarrhea are the stool becomes liquid and the frequency of bowel movements is more than three times a day and is accompanied by blood and mucus or only mucus. Saccharomyces boulardii is a probiotic yeast with proven medicinal benefits, especially in the gastrointestinal tract and antibiotic booster. Objectives: To describe the effect of Saccharomyces boulardii supplementation on the incidence of diarrhea in toddlers. Methods: Literature review method with 11 articles (2011-2021) and the keywords used are "Saccharomyces boulardii, diarrhea, toddler". Journal search with Google scholar, Scopus and Pubmed. Reputable journals SINTA S1 with 1, Scopus Q1 with 3 articles, Q2 with 2 articles, Q4 with 5 articles. Results: The results of the literature review showed that as many as ten articles (90.9%) stated that Saccharomyces boulardii supplementation had a significant effect on reducing the duration of diarrhea in children under five. In addition to the effect on the duration of diarrhea in toddlers, there are also 5 articles (45.4%) stating that there is an effect on reducing the frequency of diarrhea in toddlers on the second day after supplementation with Saccharomyces boulardii. Conclusion: There is an effect of Saccharomyces boulardii supplementation on reducing the duration and frequency of diarrhea in toddlers.Keywords: diarrhea, toddler, Saccharomyces boulardii